5‐HT4 receptors facilitate cholinergic neurotransmission throughout the murine gastrointestinal tract. Issue 8 (23rd March 2017) - Pauwelyn, V.; Lefebvre, R. A.
Abstract: Background: In the gastrointestinal tract of several species, facilitating 5‐HT4 receptors were proposed on myenteric cholinergic neurons innervating smooth muscle by in vitro study of the effect of the selective 5‐HT4 receptor agonist prucalopride on submaximal cholinergic contractions. This was not yet established in the murine gastrointestinal tract. Methods: In circular smooth muscle strips from murine fundus, jejunum and colon, contractions were induced by electrical field stimulation in the presence of guanethidine, L‐NAME and for colon also MRS 2500. Submaximal contractions were induced to study the influence of prucalopride. Key Results: Electrical field stimulation at reduced voltage induced reproducible submaximal neurogenic and cholinergic contractions as the contractions were abolished by tetrodotoxin and atropine. Hexamethonium had no systematic inhibitory effect but mecamylamine reduced the responses, suggesting that part of the cholinergic response is due to activation of preganglionic neurons. Prucalopride concentration‐dependently increased the submaximal cholinergic contractions in the three tissue types, reaching maximum from 0.03 μmol/L onwards. The facilitation in the different series with 0.03 μmol/L prucalopride ranged from 41% to 104%, 30% to 76% and 24% to 74% in fundus, jejunum, and colon, respectively. The effect of 0.03 μmol/L prucalopride was concentration‐dependently inhibited by GR 113808. Conclusions & Inferences: In the murine gastrointestinal tract, activation of 5‐HT4 receptors with prucalopride enhances cholinergic contractions, illustrating facilitation of myenteric cholinergic neurotransmission. The degree of enhancement with prucalopride is of similar magnitude as previously reported in other species, but the effective concentrations are lower than those needed in the gastrointestinal tract of other species. Abstract : In vitro studies showed that 5‐HT4 receptor stimulation enhances myenteric cholinergic neurotransmission in gastrointestinal muscle of several species, but not yet in mice. In smooth muscle strips of murine fundus, jejunum, and colon, the selective 5‐HT4 receptor agonist prucalopride enhanced electrically induced submaximal cholinergic contractions; this effect was abolished by selective 5‐HT4 receptor antagonism and confirmed with 5‐HT, illustrating that 5‐HT4 receptor stimulation also enhances murine myenteric cholinergic neurotransmission. This murine in vitro model is useful to further investigate the pharmacology and signal transduction of 5‐HT4 receptors increasing the function of myenteric cholinergic neurons.